Utilization Rate of Cakalang Fish (Katsuwonus pelamis) in Binuangeun Water, Lebak Regency, Banten Province - Awalia, Riski; Susanto, Adi; Aryani, Desy (Fakultas Pertanian, Universitas Muhammadiyah Maluku Utara, 2024)
Skipjack is one of the resource commodities utilized in Binuangeun Waters. The utilization of skipjack must be done by prioritizing its sustainability aspects. Uncontrolled skipjack fishing can have a negative impact on population sustainability so that it can result in a decrease in the number of skipjack stocks. A decrease in skipjack stock can affect the recruitment process so that it can threaten the sustainability of the resource in the future. In order to utilize the potential of skipjack in a sustainable manner, the fishing effort carried out in a body of water needs to be controlled. One of the controls that can be done is using maximum sustainable yield (MSY) data. The method used in the research is survey method. Data collection was done through observation and direct observation in the field. The results showed the lowest CPUE was 0.32102 tons/trip, and the highest CPUE was 0.892905 tons/trip. The MSY value of skipjack is 1,759 tons/year and Fopt is 4,320 trips/year. The level of utilization of skipjack has entered the overfishing category. (JTB) of skipjack in Binuangeun Waters is 1,407 tons/year.